Perception of the Multiprofessional Team on the Occupational Therapist's Performance in the Intensive Care Unit (Research, Society and Development, 2020)
Objective: This study aims to understand the perception of the multidisciplinary team of the intensive care unit about the role of the occupational therapist as part of the team and what is the understanding of these professionals about their work with the patient and their families. Methodology: This is a cross-sectional, qualitative study, carried out in an intensive care unit of a University Hospital, in the Metropolitan Region of Recife, with 14 employees of the unit. Interviews were conducted with participants about the knowledge about Occupational Therapy and its performance in the service. Results: From the analysis of the speeches of the participants, the categories were listed: Functionality, Daily Life Activity, Cognition, Family, Activity/Resource, Communication and Team, which have a direct connection to the occupational therapist in this space. Conclusion: Despite the still small visibility of the action of occupational therapy professionals in the intensive care unit, the other professionals who make up the team of this unit, expressed their perception of the performance of this professional from the use of the activity, aiming at the subject's functionality and independence, in their return to daily activities, minimizing the possible cognitive and physical sequelae.